Using Welding for Renovations of Machine Parts Made of Aluminium Alloy - Votava Jiří (Acta Technologica Agriculturae, 2014)
Due to their mechanical characteristics, aluminium alloys are materials with high potential in the automotive industry. Thus, it is useful to analyse the weldability of individual alloys, not only for possible renovations of a machine part. This paper focuses on monitoring a welded metal made by the coated electrode OK 96.20. An alloy EN AW 5754 was used as a base welding material. This base material was used in two modifications. Firstly, samples degraded in oil at a temperature of 80 °C, and secondly, samples in their standard form without grease. In the experiment, the porosity of weld beads as well as tension characteristics were analysed. In order to identify the corrosion degradation of weldments, the test was performed in compliance with the norm ČSN EN ISO 9227.